2019
DOI: 10.1039/c9cy00415g
|View full text |Cite
|
Sign up to set email alerts
|

Novozym 435: the “perfect” lipase immobilized biocatalyst?

Abstract: Novozym 435 (N435) is a commercially available immobilized lipase produced by Novozymes with its advantages and drawbacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
360
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(410 citation statements)
references
References 544 publications
(611 reference statements)
10
360
0
2
Order By: Relevance
“…Previous reports revealed that novozym 435 (a commercial immobilized Candida antarctica lipase B on polyacrylic resin) is an efficient catalyst for aza-Michael addition. [32][33][34] Furthermore, novozym 435 exhibits high thermostability in scCO 2. 35,36 Therefore, in this work, a stainless-steel vessel was employed with a working volume of 25 mL, and the aza-Michael addition catalyzed by novozym 435 was performed in scCO 2 (10 MPa) or organic solvents using benzylamine and methyl acrylate as substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports revealed that novozym 435 (a commercial immobilized Candida antarctica lipase B on polyacrylic resin) is an efficient catalyst for aza-Michael addition. [32][33][34] Furthermore, novozym 435 exhibits high thermostability in scCO 2. 35,36 Therefore, in this work, a stainless-steel vessel was employed with a working volume of 25 mL, and the aza-Michael addition catalyzed by novozym 435 was performed in scCO 2 (10 MPa) or organic solvents using benzylamine and methyl acrylate as substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports revealed that novozym 435 (a commercial immobilized Candida antarctica lipase B on polyacrylic resin) is an efficient catalyst for aza‐Michael addition . Furthermore, novozym 435 exhibits high thermostability in scCO 2.…”
Section: Resultsmentioning
confidence: 99%
“…CALB was utilized both as lyophilized enzyme and immobilized as Novozym 435. The latter preparation is most commonly employed, both in the laboratory and on industrial scale [43]. BSLA and CALB were produced by expressing the codon-optimized genes in E.coli BL21 (DE3) within pET22b.…”
Section: Bsla Activity In Dry Organic Solventsmentioning
confidence: 99%
“…For instance, the lipase B from Candida antarctica immobilized on acrylic resin (Novozyme 435, herein referred to as immobilized CALB) is one of the most applied biocatalysts, used in esterification, transesterification and hydrolysis reactions. Some of these applications have been detailed in a recent review by Fernandez‐Lafuente and co‐workers …”
Section: Lipase‐catalyzed Mechanoenzymatic Reactions By Ball Millingmentioning
confidence: 99%
“…Some of these applications have been detailed in ar ecent review by Fernandez-Lafuente and co-workers. [59] 2.1. CALB-catalyzed resolution of secondary alcohols by acetylation Hernµndez et al reportedt he first mechanochemical reactions catalyzed by immobilizedC ALB without anya queous or organic solvents.…”
Section: Lipase-catalyzed Mechanoenzymatic Reactions By Ball Millingmentioning
confidence: 99%